Activation Products of the Haemostatic System in Coronary, Cerebrovascular and Peripheral Arterial Disease - van der Bom, J. G.; Bots, M. L.; Haverkate, F.; Meijer, P.; Hofman, A.; Kluft, C.; Grobbee, D. E. (Thrombosis and Haemostasis, 2001)
To determine the presence of a ‘hypercoagulable state’ as assessed by indices of thrombin and plasmin generation and of the amount of fibrin that is lysed, in patients with stable coronary, cerebral and peripheral arterial disease a population-based cross-sectional study was performed. From a population-based cohort comprising 7983 men and women aged 55 years and over, we randomly selected 127 subjects with a history of myocardial infarction, 124 with a history of stroke and/or transient ischemic attack, 131 patients with peripheral arterial disease and 263 control subjects in the same age group without arterial disease. Subjects using anticoagulant drugs were not selected. F1+2, TAT, and PAP were not associated with a history of cardiovascular events, nor with peripheral arterial disease. In contrast, positive associations were found for D-Dimer. Mean D-Dimer level was 40 μg/l (95% CI 35,44) in control subjects; 53 μg/l (47, 61) in those with a history of myocar-dial infarction and 51 μg/l (45, 58) in those with a history of stroke and or transient ischemic attack. D-Dimer increased gradually with increasing severity of peripheral atherosclerosis; a decrease in ankle/arm systolic blood pressure ratio of 0.1 was associated with an increase in D-Dimer of 3.9 μg/l (p<0.01). This was more pronounced in subjects with higher F1+2, TAT and PAP concentration. In conclusion, the markers of onset of coagulation F1+2, TAT and PAP are not associated with the presence of arterial disease, but increased levels of these markers are necessary for the positive association between D-Dimer and arterial disease.
Keywords: D-Dimer; prothrombin fragment 1+2; thrombin-antithrombin; plasmin-antiplasmin; fibrinolysis; cardiovascular risk; hypercoagulation; hypofibrinolysis